2015
DOI: 10.1093/ehjci/jev246
|View full text |Cite
|
Sign up to set email alerts
|

Incremental value of quantitative CMR including parametric mapping for the diagnosis of acute myocarditis

Abstract: NCT02299856.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
146
4
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(162 citation statements)
references
References 34 publications
10
146
4
2
Order By: Relevance
“…18 In the meantime, T1 mapping has been introduced and histologically validated to detect diffuse myocardial damage. 12 Several studies have already reported the additive value of elevated native T1 relaxation times in subjects with acute myocarditis, achieving a diagnostic accuracy of 61% to 99%, 13,15,16,27 and the present study came to a result in between this range (78%). The cutoff, which discriminated best acute myocarditis subjects from healthy controls, was 980 ms, which is in the range of the 990 ms reported by Ferreira et al, 13 992 ms by Hinojar et al, 15 and 1000 ms by Luetkens et al 16 At acute presentation, the elevated native T1 less probably represents fibrosis, but edema, hyperemia, and myocardial necrosis.…”
Section: Von Knobelsdorff-brenkenhoff Et Al T1 and T2 Mapping Myocardsupporting
confidence: 67%
See 3 more Smart Citations
“…18 In the meantime, T1 mapping has been introduced and histologically validated to detect diffuse myocardial damage. 12 Several studies have already reported the additive value of elevated native T1 relaxation times in subjects with acute myocarditis, achieving a diagnostic accuracy of 61% to 99%, 13,15,16,27 and the present study came to a result in between this range (78%). The cutoff, which discriminated best acute myocarditis subjects from healthy controls, was 980 ms, which is in the range of the 990 ms reported by Ferreira et al, 13 992 ms by Hinojar et al, 15 and 1000 ms by Luetkens et al 16 At acute presentation, the elevated native T1 less probably represents fibrosis, but edema, hyperemia, and myocardial necrosis.…”
Section: Von Knobelsdorff-brenkenhoff Et Al T1 and T2 Mapping Myocardsupporting
confidence: 67%
“…Moreover, the general level of ECV was lower in this study as compared with that in other studies. Although in the present study an ECV of 0.24 achieved the best results, this cutoff was 0.29 in the studies by Luetkens et al 16 and by Radunski et al 27 This discrepancy may be explained by differences in the T1 techniques, timing of the postcontrast T1 maps, as well in the patient samples. For example, the population of the present study was younger as the one by Radunski et al 27 and had a higher ejection fraction (60% vs. 42%).…”
Section: Von Knobelsdorff-brenkenhoff Et Al T1 and T2 Mapping Myocardcontrasting
confidence: 66%
See 2 more Smart Citations
“…Using T1 values before and after administration of an extracellular contrast agent, allows the additional calculation of the extracellular volume (ECV), well-established in cardiac MRI 8. As liver fibrosis is defined by an increase of extracellular matrix,1 ECV is a physiologically intuitive unit of measurement, independent of field strength and thus suitable for follow-up examinations using different scan sites.…”
mentioning
confidence: 99%